2017
DOI: 10.2147/jbm.s142189
|View full text |Cite
|
Sign up to set email alerts
|

Age- and sex-related changes in hematological parameters in healthy Malawians

Abstract: AimThe aim of the study was to determine how values for white blood cell (WBC) counts, hemoglobin (Hb), hematocrit (Hct), mean corpuscular volume (mcv), and platelet counts vary with age and sex in healthy Malawians.MethodsWe recruited 660 (316 male and 344 female) participants in 12 different age groups. An ethylenediaminetetraacetic acid-anticoagulated blood sample collected from each participant was analyzed using a hematological analyzer.ResultsWBC counts decreased with age with the lowest counts observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 20 publications
(43 reference statements)
3
21
0
2
Order By: Relevance
“…Methylprednisolone was used in the present study since other synthetic corticosteroids are not available in Denmark for intramuscular injection following surgical removal of M3. Methylprednisolone is classified as intermediate duration of action with plasma half-life time of 3 to 4 hours and duration of action of 12 to 36 hours [ 24 ]. Consequently, peripheral blood samples were obtained before surgery and after three days, when methylprednisolone’s duration of action of was ended and haematological parameters were anticipated to be normalized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Methylprednisolone was used in the present study since other synthetic corticosteroids are not available in Denmark for intramuscular injection following surgical removal of M3. Methylprednisolone is classified as intermediate duration of action with plasma half-life time of 3 to 4 hours and duration of action of 12 to 36 hours [ 24 ]. Consequently, peripheral blood samples were obtained before surgery and after three days, when methylprednisolone’s duration of action of was ended and haematological parameters were anticipated to be normalized.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly patients are characterized by decreased level of haemoglobin and leucocytes in peripheral blood [ 24 , 26 , 31 ]. In the present study, there were no significant differences in the level of haemoglobin and leucocytes, when the results were correlated for age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cr and BUN induce the same effects in males and females ( 48 53 ). The results of studies investigating WBC levels are inconsistent; certain studies indicate that WBC levels are higher in males ( 54 , 55 ), whereas others indicate that WBC levels are higher in females ( 56 , 57 ). However, major influential factors include age and sex hormone levels; indeed, it has been suggested that WBC levels may change in females at different stages of the menstrual cycle ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, because the participant ages averaged 53.50 years, it is possible that old age might be the influencing factor for the effect seen in the hematological indices. 26,27 In this study, pesticide and non-pesticide-using farmer groups did not show significantly affected hemoglobin and hematocrit levels compared to the control and nor- mal range levels. However, surveillance and caution must be maintained in the use of pesticides.…”
Section: Discussionmentioning
confidence: 46%